Pemberdayaan Lansia dalam Melakukan Aktivitas Fisik Senam Lansia untuk Meningkatkan Tingkat Kemandirian Lansia - Putra, I Gede Yudiana; Muryani, Ni Made Sri; Artawan, I Kadek (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2024)
Background: Aging leads to physical deterioration, which makes the elderly dependent on others for daily activities. One way to increase their independence is through physical activities such as elderly gymnastics. Regular participation in elderly gymnastics can restore physical function, improve joint, muscle, and movement coordination, and enhance heart function, leading to a healthier and fitter body. Method: The program began with a preparation stage, followed by elderly gymnastics training and counseling. This activity took place in one session, targeting both independent and assisted elderly individuals. The elderly gymnastics included basic exercises with a warm-up, core movements, and cooling down, lasting approximately 15-30 minutes. Afterward, an evaluation of the activity was conducted. Results: A total of 60 elderly individuals participated in the gymnastics session, which included warm-up, core, and cooling exercises. The participants appeared enthusiastic and easily followed the movements, especially with music accompaniment. However, some had difficulty with foot movements due to balance issues. After the gymnastics session, counseling was provided on the importance of doing elderly gymnastics independently. The elderly were very engaged during the counseling and asked several questions afterward. Conclusion: Elderly gymnastics can be incorporated as a routine activity in elderly health programs like posyandu, helping the elderly become more independent with a healthy and fit body. Regular participation in these exercises can improve their ability to perform daily activities independently.